Procedimentos metodológicos em dissertações de mestrados profissionais na área de ciências sociais aplicadas: estudos de casos múltiplos no campo de públicas - Vitalino, Adriana Lucia (2019)
The objective of this study was to identify the methodological option of the authors of the Master’s Theses of Professional Masters in Public Administration from Federal Institutions of Education, from 2013 to 2016. And contribute with the characterization of the profile of the research in the Professional Masters from the Field of Public Administration Brazilian. In order to identify the methodological approaches used in the master's theses, six categories of methodological analysis were established: research focus (or how to approach the problem), research objective, research strategy, research source / environment, data collection instrument. And nature of the research problem. The study sample comprised 76 master's theses which were analyzed using qualitative and quantitative methods. The methodologies procedures used were the bibliographical research, documentary and content analysis and statistics. The results showed that the qualitative approach (42%) was the most used in relation to the qualitative and quantitative studies (34%) and quantitative (24%); the descriptive objectives were found in 49% of master's theses; research strategy case study had the highest number of occurrences, 43 (57%); as to the research environment, it was found that 83% of MSc thesis are of field, the interview (33%), the questionnaire (27%) and multiple instruments (37%) were used as data collection instruments; As to the nature of the research problem, the applied nature was identified in 80% of the master's theses. Analysis of the master's theses showed that the authors prioritized qualitative descriptive studies, of an applied nature, with field research data; and research strategy case study. It is pointed out that the master theses analyzed established a relation to the theoretical elements of this study. It is considered that this study can contribute to the reflection of students, professional programs of the field of public administration and stakeholder other interested about the methodological procedures used in the master's theses and identify opportunities for improvements in research designs. And it points out directions for new research in the Field of Public Administration Brazilian.